'Are We Talking as Professionals or as Parents?' Complementary views on supervisory neglect among professionals working with families in Quebec, Canada. (November 2020) - Grégoire-Labrecque, Geneviève; Lafantaisie, Vicky; Trocmé, Nico; Lacharité, Carl; Li, Patricia; Audet, Geneviève; Sullivan, Richard; Ruiz-Casares, Mónica
Highlights: Personal and professional experiences influence understandings of supervisory neglect. Importance of culture, personal experiences, and self-awareness in decision-making. Reconciling professional and personal dimensions for ethical decision-making. Abstract: This paper addresses how personal and professional values and experiences of professionals working with children and families from diverse cultural backgrounds interweave in their understanding of (in)adequate child supervision and how this influences their decision-making around supervisory neglect. Eleven focus group discussions involving 67 service providers were held in two of the largest cities in the province of Quebec, Canada. Participants were recruited through public school boards, municipal police agencies, child protection agencies, and health and social services. Service providers who were recruited to offer their professional perspective on children's supervision, responded with examples from both their professional and personal contexts. Whereas personal examples, including those related to culture, were used to qualify, contextualize, deepen analysis, and better assess the boundaries of a supervisory situation, professional examples were used to refer to the legal sphere. Besides using professional decision-making tools, service providers could benefit from incorporating their personal experiences to advance reflection about supervisory neglect and from reconciling their professional and personal dimensions for more ethical decision-making in this field. The latter would require clinical (not just administrative) support, a good network of colleagues, and training. Seeking depth and sensitivity beyond what structured decision grids allow is particularly needed in ethnoculturally diverse contexts.